Association of masked uncontrolled hypertension and cardiovascular diseases in treated hypertensive patients - Shi, Xiaoyang (Arch Med Sci, 2019)
INTRODUCTION: The aim of the study was to evaluate the association of masked uncontrolled hypertension (MUCH) and prevalence of cardiovascular disease in treated hypertensive patients. MATERIAL AND METHODS: Patients’ demographics and prior medical histories were collected. Fasting venous blood was drawn for evaluation of serum creatinine level, which was used to calculate glomerular filtration rate (GFR). Clinic blood pressure (BP) and 24 h ambulatory blood pressure monitoring (ABPM) measurements were performed. Based on the clinic BP and 24 h ABPM results, patients were divided into MUCH and non-masked hypertension groups. RESULTS: Compared to patients without masked hypertension, MUCH patients were older (62.4 ±11.2 vs. 59.7 ±10.4 years, p < 0.05), more likely to be male (66.9% vs. 63.4%), had diabetes (33.9% vs. 29.6%), longer hypertension duration (12.4 ±5.3 vs. 9.5 ±4.5 years, p < 0.05), lower GFR (79.5 ±11.6 vs. 82.4 ±10.3 ml/min/1.73 m(2), p < 0.05), treated with β-blocker (39.0% vs. 32.7%, p < 0.05) and required more antihypertensive medications (2.7 ±0.5 vs. 2.2 ±0.3, p < 0.05). MUCH patients have higher cardiovascular disease prevalence than that without masked hypertension (30.1% vs. 23.4%, p < 0.05). After adjustment for covariates, MUCH was still independently associated with higher cardiovascular disease prevalence with odds ratio 1.38 (95% confidence interval 1.17–1.62, p < 0.05). CONCLUSIONS: The MUCH is independently associated with prevalent cardiovascular disease in treated hypertensive patients. Future studies are needed to evaluate whether correction of MUCH can improve patients’ outcomes.